DNAJB6 isoform specific knockdown: Therapeutic potential for limb girdle muscular dystrophy D1 - Andrew R. Findlay; May M. Paing; Jil A. Daw; Meade Haller; Rocio Bengoechea; Sara K. Pittman; Shan Li; Feng Wang; Timothy M. Miller; Heather L. True; Tsui-Fen Chou; Conrad C. Weihl (Elsevier, 2023)
Dominant missense mutations in DNAJB6, a co-chaperone of HSP70, cause limb girdle muscular dystrophy (LGMD) D1. No treatments are currently available. Two isoforms exist, DNAJB6a and DNAJB6b, each with distinct localizations in muscle. Mutations reside in both isoforms, yet evidence suggests that DNAJB6b is primarily responsible for disease pathogenesis. Knockdown treatment strategies involving both isoforms carry risk, as DNAJB6 knockout is embryonic lethal. We therefore developed an isoform-specific knockdown approach using morpholinos. Selective reduction of each isoform was achieved in vitro in primary mouse myotubes and human LGMDD1 myoblasts, as well as in vivo in mouse skeletal muscle. To assess isoform specific knockdown in LGMDD1, we created primary myotube cultures from a knockin LGMDD1 mouse model. Using mass spectrometry, we identified an LGMDD1 protein signature related to protein homeostasis and myofibril structure. Selective reduction of DNAJB6b levels in LGMDD1 myotubes corrected much of the proteomic disease signature toward wild type levels. Additional in vivo functional data is required to determine if selective reduction of DNAJB6b is a viable therapeutic target for LGMDD1.